2008
DOI: 10.1016/j.dnarep.2008.06.015
|View full text |Cite
|
Sign up to set email alerts
|

DNA-PK and ATM phosphorylation sites in XLF/Cernunnos are not required for repair of DNA double strand breaks

Abstract: Nonhomologous end joining (NHEJ) is the major pathway for the repair of DNA double strand breaks (DSBs) in human cells. NHEJ requires the catalytic subunit of the DNA-dependent protein kinase (DNA-PKcs), Ku70, Ku80, XRCC4, DNA ligase IV and Artemis, as well as DNA polymerases μ and λ and polynucleotide kinase. Recent studies have identified an additional participant, XLF, for XRCC4-like factor (also called Cernunnos), which interacts with the XRCC4-DNA ligase IV complex and stimulates its activity in vitro, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 37 publications
(62 reference statements)
7
110
1
Order By: Relevance
“…Consistent with this hypothesis, removal of additional residues (serines/ threonines followed by prolines, aspartates, glycines, and glutamates, Fig. S3A) that are targeted in a number of substrates of ATMlike kinases in vivo [38][39][40][41][42] completely abrogated Xrs2 phosphorylation in response to DNA damaging agents (i.e., xrs2-27A, Fig. S3B).…”
Section: Cdk1 Is An Mrx Kinasesupporting
confidence: 62%
See 1 more Smart Citation
“…Consistent with this hypothesis, removal of additional residues (serines/ threonines followed by prolines, aspartates, glycines, and glutamates, Fig. S3A) that are targeted in a number of substrates of ATMlike kinases in vivo [38][39][40][41][42] completely abrogated Xrs2 phosphorylation in response to DNA damaging agents (i.e., xrs2-27A, Fig. S3B).…”
Section: Cdk1 Is An Mrx Kinasesupporting
confidence: 62%
“…This result is consistent with the observation that members of the ATM/ATR family of kinases-like many other kinases-are sometimes capable of phosphorylating substrates on residues that do not fit their canonical consensus motif. [39][40][41][42] It is also important to note that Xrs2 has been predicted to be a target of Rad53 kinase, a central effector of the Tel1/Mec1-dependent checkpoint response. 56 Although this prediction remains to be verified, it is possible that a small, but nevertheless significant, fraction of Xrs2 DNA damage-dependent phosphorylation may be catalyzed by Rad53, thereby explaining the involvement of non-consensus Tel1 sites in this phosphoregulatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Previous NHEJ models suggested that after binding of Ku to DNA ends, DNA-PKcs binds Ku:DNA to form a DNA-PK holoenzyme and bridges the broken ends (15)(16)(17)(18); however, recent experiments indicate that DNAPKcs may have different roles in NHEJ, such as the stabilization of core NHEJ factors, recruitment and retention of accessory factors, involvement in the DDR signaling cascade, and repair of complex and clustered DSBs (19)(20)(21)(22)(23)(24)(25). In addition, recent structural studies have shown that XRCC4 and XLF form filamentous structures in vitro (26)(27)(28).…”
mentioning
confidence: 99%
“…In addition to its catalytic function at the DSB ends, DNA-PKcs may also tether the broken DNA ends to facilitate rejoining (Meek et al, 2004). Although the DNA-PKcs kinase activity catalyzes the phosphorylation of many NHEJ related substrates, the phosphorylation of the DNA-PKcs itself is the only physiologically relevant event identified so far Cruet-Hennequart et al, 2008;Otsuki et al, 2007;Soubeyrand et al, 2006;Yu et al, 2008). DNA-PKcs autophosphorylation appears to be important for DSB repair as DNA-PKcs mutated at key phosphorylation sites (T2609 and S2056 at ABCDE and PQR clusters respectively) is impaired in its function in D-NHEJ (Cui et al, 2005;Meek et al, 2007).…”
Section: When Effectiveness Is Chosen Over Accuracy: Dna-pkcs Dependementioning
confidence: 99%
“…DNA-PKcs is a serine/threonine kinase with specificity for S/TQ sites (Marshall, 2011) that regulates its activity through autophosphorylation. It targets, RPA2, WRN, Cernunnos/XLF, LigIV, and XRCC4 Cruet-Hennequart et al, 2008;Otsuki et al, 2007;Soubeyrand et al, 2006;Yu et al, 2008). In addition to its catalytic function at the DSB ends, DNA-PKcs may also tether the broken DNA ends to facilitate rejoining (Meek et al, 2004).…”
Section: When Effectiveness Is Chosen Over Accuracy: Dna-pkcs Dependementioning
confidence: 99%